2019
DOI: 10.1103/physreva.99.033827
|View full text |Cite
|
Sign up to set email alerts
|

Tunable single-photon quantum router

Abstract: We propose an efficient single-photon router comprising two resonator waveguide channels coupled by several sequential cavities with embedded three-level atoms. We show that the system can operate as a perfect four-way single-photon switch. We also demonstrate that an incident single photon propagating in one of the waveguides can be routed into one or the other output channels; such routing can be controlled by the external classical electromagnetic field driving the atoms. We argue that, under appropriate co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 30 publications
4
21
0
Order By: Relevance
“…To demonstrate the feasibility of such routing, we consider the dynamics of the wave packet (4) centered at k 0 = arccos (−E 0 /2) ≈ 1.33 and having the width ∆E = 0.02 in Second, we address the system in the wave packet "1/4-splitting" regime. As was demonstrated recently [30], the stationary transmission and reflection spectra of the considered system have wide flat sub-bands in the vicinity of E = ±Ω. Within these sub-bands, the probabilities of scattering into the four possible channels (A L , A R , B L , and B R ) are all approximately equal to 1/4 (see panel (g) of Fig.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…To demonstrate the feasibility of such routing, we consider the dynamics of the wave packet (4) centered at k 0 = arccos (−E 0 /2) ≈ 1.33 and having the width ∆E = 0.02 in Second, we address the system in the wave packet "1/4-splitting" regime. As was demonstrated recently [30], the stationary transmission and reflection spectra of the considered system have wide flat sub-bands in the vicinity of E = ±Ω. Within these sub-bands, the probabilities of scattering into the four possible channels (A L , A R , B L , and B R ) are all approximately equal to 1/4 (see panel (g) of Fig.…”
supporting
confidence: 65%
“…Such a system with 12 atoms forming the junction was studied recently in Ref. [30], where it is demonstrated that it has promising scattering properties in the stationary regime for certain sets of parameters. In this paper, we address the dynamics of wave packets for the most relevant parameter sets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45][46][47][48][49][50][51] Optical router is a key element for controlling the path of signal flow in quantum and classical network. Recently, quantum router has been proposed in various systems, that is, cavity atom, [52][53][54][55][56][57][58][59][60] coupled resonator [61,62] and optomechanical systems. [63][64][65] Previous schemes demonstrated with optomechanical systems via a red-detuned control field have some restrictions, such as there is only one output terminal, or the probability of successful routing decreases with increasing the number of routing ports.…”
Section: Introductionmentioning
confidence: 99%
“…There has also been a series of routing proposals reported which are based on QEs embedded in coupled resonator waveguides (Refs. [6][7][8][9][10] to name a few). In other proposals circuit quantum electrodynamics QED systems have been used to attain routing through EIT (see, for example, Ref.…”
Section: Introductionmentioning
confidence: 99%